Analisis Penerapan Islamic Social Reporting dan Tata Kelola Lembaga Keuangan Mikro Syariah dalam Mendorong Mobilitas Sosial Nasabah - Yaya, Rizal; Purnami, Kartika Dewi (Jati: Jurnal Akuntansi Terapan Indonesia, 2020)
This research aims to evaluate the implementation of Islamic Social Reporting (ISR) and governance in the Islamic micro-finance institutions in encouraging the movement of social mobility. The object of this study consists of two Islamic microfinance institutions: Islamic Micro Finance (BMT) BIF and Islamic Rural Bank (BPRS) BDW. The subjects of this research were staff and costumers of Islamic microfinance institutions. This research used qualitative descriptive method. Based on the analysis conducted both institutions provide funding for their costumers based on Islamic contract and mostly for working capital. The financing procedure was through collection of customer’s identity, conducting surveys and contract singing. The installment to BMT BIF and BPRS BDW was made by the customers in two ways: the customers pay to the marketing person who came to visit them or the customer comes to the office of BMT BIF and BPRS BDW. Social activities in both institutions are relatively similar such as scholarships, donations for orphans, sponsorship of the institutions related to Muhammadiyah. The social activity reporting format are different in both institution. BMT BIF social responsibility activities are reported specifically in the BMT Annuat General Meeting (RAT), mean while the BPRS BDW has not made specifif social responsibility reporting for their Annual General Meeting. From financing and social responsibility both institutions have been able to assist the movement of social mobility in society, especially in customers, it can be seen from costumers that initially did not have a business then now can have a business and still growing. Moreover, their costumers can survived from moneylenders trap. In terms of ISR compliance reporting for both institutions, the BMT BIF has met 70%-80% compliance, while BPRS BDW 50% compliance.